THE POWER OF PROVERBS IN LANGUAGE, CULTURE, AND COMMUNICATION (Proceedings of International Educators Conference, 2024)
This article gives information about the history of proverbs and why they are important in human life. Proverbs are short sayings that give advice or share wisdom. The article also looks at where proverbs come from, how they have changed over time, and their importance in today’s world. Drawing on powerful insights from professional scientists, the article examines the cognitive and social benefits of using proverbs in speech and writing. The article also explains how using proverbs can help our brains and relationships with others. By giving examples of well-known proverbs and what they mean, I show how these sayings contain valuable lessons that apply to everyone, no matter where they come from. In the end, the article highlights how proverbs have a big impact on the way we speak, our cultures, and how we connect with each other.